2013
DOI: 10.1063/1.4848775
|View full text |Cite
|
Sign up to set email alerts
|

Geometric solitons of Hamiltonian flows on manifolds

Abstract: It is well-known that the LIE(Locally Induction Equation) admit soliton-type solutions and same soliton solutions arise from different and apparently irrelevant physical models. By comparing the solitons of LIE and Killing magnetic geodesics, we observe that these solitons are essentially decided by two families of isometries of the domain and the target space respectively. With this insight, we propose the new concept of geometric solitons of Hamiltonian flows on manifolds, such as geometric Schr\"odinger flo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Further on, Barros et al in [9] showed that these curves are solitons of the localized induction equation (LIE). A more global and geometric view on the connection between solitons of LIE and magnetic curves are provided in [29].…”
Section: Introductionmentioning
confidence: 99%
“…Further on, Barros et al in [9] showed that these curves are solitons of the localized induction equation (LIE). A more global and geometric view on the connection between solitons of LIE and magnetic curves are provided in [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, from the viewpoint of differential geometry C. Song, X. Sun and Y. Wang [15] propose a notion "geometric soliton", which is concerning special solutions for some geometric flows and can be regarded as a geometric generalization of the classical solitary wave solutions. In the present paper, we also use the similar method to study (1)- (4).…”
Section: Ruiqi Jiang Youde Wang and Jun Yangmentioning
confidence: 99%
“…We have transformed all problems to two-dimensional elliptic cases which are suitable variances of (15). Furthermore, we can choose real constants c i 's and ω i 's such that µ is a small positive constant, which gives a small parameter ε > 0 by the relation µ = ε or µ = ε| log ε|.…”
Section: Remarkmentioning
confidence: 99%
“…For details we refer to [4]. Such a special class of periodic solutions can also be called as "geometric solitons" in [11,12]. For the case M ≡ R 2 and H(u) ≡ G(d(u)), where d(u) denotes the geodesic distance from u ∈ S 2 to the north pole P = (0, 0, 1), we would like to consider the equivariant solutions to (6.1) written by u(x, t) = (sin h(r) cos(mθ + wt), sin h(r) sin(mθ + wt), cos h(r)), (…”
Section: It Deduces That Limmentioning
confidence: 99%